The model of school leadership in Italy - Nicolosi, Anna Maria (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
The important, yet complex, figure of the school principal in the Italian education system still seems to be characterized by several specific elements nowadays, mainly outlining their role and bureaucratic-administrative functions, and partly also the aspects related to educational-didactic leadership. The aim of this article is to focus on the leadership of the school principal by sketching their profile as well as the leadership style in the Italian context, thus highlighting their tasks, management, organizational responsibilities, and the capacity for planning as a lever to innovate and improve within the educational context in which they operate.
Keywords: school principal; leadership; autonomy; management; school organization; educational innovation